Math, asked by nidhipandey520, 11 months ago

x²+27+72 factories ​

Answers

Answered by chhotiroy343
0

Answer:

x^2+27+72

x^2+99

x^2=-99

x =  \frac{ + }{ - }  \:  \sqrt{99}

x =  \frac{ + }{ - }  \: 3 \sqrt{11}

Answered by Anonymous
1

Answer:

Step-by-step explanation:

Factoring  x2+27x+72  

The first term is,  x2  its coefficient is  1 .

The middle term is,  +27x  its coefficient is  27 .

The last term, "the constant", is  +72  

Step-1 : Multiply the coefficient of the first term by the constant   1 • 72 = 72  

Step-2 : Find two factors of  72  whose sum equals the coefficient of the middle term, which is   27 .

     -72    +    -1    =    -73  

     -36    +    -2    =    -38  

     -24    +    -3    =    -27  

     -18    +    -4    =    -22  

     -12    +    -6    =    -18  

     -9    +    -8    =    -17  

     -8    +    -9    =    -17  

     -6    +    -12    =    -18  

     -4    +    -18    =    -22  

     -3    +    -24    =    -27  

     -2    +    -36    =    -38  

     -1    +    -72    =    -73  

     1    +    72    =    73  

     2    +    36    =    38  

     3    +    24    =    27    That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above,  3  and  24  

                    x2 + 3x + 24x + 72

Step-4 : Add up the first 2 terms, pulling out like factors :

                   x • (x+3)

             Add up the last 2 terms, pulling out common factors :

                   24 • (x+3)

Step-5 : Add up the four terms of step 4 :

                   (x+24)  •  (x+3)

            Which is the desired factorisation

Similar questions